Parkinson's-adapted cognitive stimulation therapy: a pilot randomized controlled clinical trial. (July 2019) - Leroi, Iracema; Vatter, Sabina; Carter, Lesley-Anne; Smith, Sarah J.; Orgeta, Vasiliki; Poliakoff, Ellen; Silverdale, Monty A.; Raw, Jason; Ahearn, David J.; Taylor, Christine; Rodda, Joanne; Abdel-Ghany, Tarek; et al.
Cognitive stimulation therapy (CST) is widely used with people with dementia, but there is no evidence of its efficacy in mild cognitive impairment or dementia in Parkinson's disease (PD-MCI; PDD) or dementia with Lewy bodies (DLB). We aimed to explore the impact of 'CST-PD', which is home-based, individualized CST adapted for this population. In a single-blind, randomized controlled exploratory pilot trial (RCT), we randomized 76 participant–dyads [PD-MCI ( n = 15), PDD ( n = 40), DLB ( n = 21) and their care partners] to CST-PD or treatment as usual (TAU). CST-PD involves home-based cognitively stimulating and engaging activities delivered by a trained care partner. Exploratory outcomes at 12 weeks included cognition (Addenbrooke's Cognitive Evaluation; ACE-III), neuropsychiatric symptoms and function. In care partners, we assessed burden, stress and general health status. Relationship quality and quality of life were assessed in both dyad members. At 12 weeks, the ACE-III showed a nonstatistically significant improvement in the CST-PD group compared with the TAU group, although neuropsychiatric symptoms increased significantly in the former. In contrast, care partners' quality of life ( d = 0.16) and relationship quality ('satisfaction', d = 0.01; 'positive interaction', d = 0.55) improved significantly in the CST-PD group, and care burden ( d = 0.16) and stress ( d = 0.05) were significantly lower. Qualitative findings in the CST-PD recipients revealed positive 'in the moment' responses to the intervention, supporting the quantitative results. In conclusion, care-partner-delivered CST-PD may improve a range of care-partner outcomes that are important in supporting home-based care. A full-scale follow-up RCT to evaluate clinical and cost effectiveness is warranted.